Intangible cultural heritage and the better angels of folklore's nature. Issue 8 (13th September 2016) - Hansen, Gregory
Abstract: Folklore research in the United States typically is completed either through academic departments or in organisations designed to create public presentations of traditional expressive culture. These two approaches are termed 'academic folklore' and 'public folklore'. The intellectual history of both approaches has recently been critiqued. One result of this deconstruction is an ambivalence over the historical legacy of key concepts in the study of folklore. Assessing elements of the critical study of folklore's history – in both academe and the public sector – suggests opportunities for reconstituting the study of traditional culture to establish a more socially responsive approach that is relevant to ways that heritage professionals assess folklore as intangible culture heritage.